Changing risk factors for hepatocellular carcinoma in hyperendemic regions in the era of universal hepatitis B vaccination. (August 2020) - Wang, Xue-Yan; Huang, Jin-Mei; Lu, Xue-Ming; Harrison, Tim J.; Liu, Hua-Bing; Jia, Hui-Hua; Fang, Zhong-Liao
Highlights: Hepatitis B vaccination at birth has reduced their risk of developing liver cancer. Hepatitis B vaccination could not prevent all liver cancer cases. The major risk factor of liver cancer in hyperendemic regions is changing. Abstract: Background: LongAn, Guangxi, was the first county in China to implement universal childhood hepatitis B virus (HBV) immunization. We aimed to determine its long-term effects in preventing hepatocellular carcinoma (HCC) 32 years after the immunization programme was launched. Methods: Information on HCC deaths for LongAn and its neighbouring county, BinYang (where universal hepatitis B vaccination was not started till 2002), were obtained from the national mortality surveillance system. The data were analysed using Poisson regression. Results: The overall age-adjusted mortalities of HCC in LongAn and BinYang during 2017–2018 were 53.3/100, 000 and 45.4/100, 000, respectively. The mortality of males aged 20–29 years in LongAn, who were vaccinated at birth, was lower (2.7/100, 000, 95%CI 0.8–4.5) than that of males in BinYang, who were not vaccinated (4.7/100, 000, 95%CI 3.2–6.3). In LongAn, the HCC mortality in adults aged 20–29 years declined significantly from 7.9/100, 000 (95%CI 4.4–11.4) in 2004 to 1.4/100, 000 (95%CI 0.4–2.4) in 2017–2018 (χ 2 = 5.554, p = 0.018). Among those vaccinated at birth, the HCC mortality in mountainous areas, where dietary exposure to aflatoxins is more common, is higher (9.0/100, 000, 95%CI 4.5–13.5) than in low-lying areas (6.5/100, 000, 95%CI 3.6–9.4) (χ 2 = 0.2393, p = 0.618). Conclusion: Immunization of infants against HBV has reduced their risk of developing HCC as children and young adults but could not prevent all cases of HCC, suggesting that the major risk factor for HCC in hyperendemic regions is shifting from HBV to other factors. Additional prevention strategies for HCC will be needed in the future.